2017
DOI: 10.1080/14764172.2017.1334923
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the efficiency of Er,Cr:YSGG laser and diode laser on human β-defensin-1 and IL-1β levels during the treatment of generalized aggressive periodontitis and chronic periodontitis

Abstract: The use of the Er,Cr:YSGG laser at non-surgical periodontal treatment decreased both IL-1β and human β-defensin-1 levels. It is likely that Er,Cr:YSGG laser is more suitable for the treatment of generalized aggressive periodontitis and chronic periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 38 publications
1
22
0
1
Order By: Relevance
“…A number of studies have reported the outcomes of LLLT in the treatment of AgP with conflicting results . A recent clinical study by Annaji et al showed that clinical and immunological outcomes were significantly better for the LLLT group compared to the SRP group at follow up .…”
Section: Introductionmentioning
confidence: 72%
See 4 more Smart Citations
“…A number of studies have reported the outcomes of LLLT in the treatment of AgP with conflicting results . A recent clinical study by Annaji et al showed that clinical and immunological outcomes were significantly better for the LLLT group compared to the SRP group at follow up .…”
Section: Introductionmentioning
confidence: 72%
“…Of these 10 studies, six were further excluded. After the final stage of selection, four studies were included and processed for data extraction . The study identification flowchart according to PRISMA guidelines and reasons for article exclusion are shown in Figure …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations